2022
DOI: 10.5194/acp-22-11155-2022
|View full text |Cite
|
Sign up to set email alerts
|

Modeling approaches for atmospheric ion–dipole collisions: all-atom trajectory simulations and central field methods

Abstract: Abstract. Ion–dipole collisions can facilitate the formation of atmospheric aerosol particles and play an important role in their detection in chemical ionization mass spectrometers. Conventionally, analytical models, or simple parametrizations, have been used to calculate the rate coefficients of ion–dipole collisions in the gas phase. Such models, however, neglect the atomistic structure and charge distribution of the collision partners. To determine the accuracy and applicability of these approaches under a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…We have previously shown that the central field approach yields very similar results to those from sampling collision trajectories using MD, provided that the attractive interaction used in the central field model is fitted to the tail of the potential of mean force (PMF) between the collision partners (Neefjes et al, 2022). The largest collision partners studied in that study were, however, dimers.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…We have previously shown that the central field approach yields very similar results to those from sampling collision trajectories using MD, provided that the attractive interaction used in the central field model is fitted to the tail of the potential of mean force (PMF) between the collision partners (Neefjes et al, 2022). The largest collision partners studied in that study were, however, dimers.…”
Section: Introductionmentioning
confidence: 80%
“…Molecular dynamics (MD) simulations allow us to study the time evolution of collision systems, where all intra-and intermolecular interactions are described through force fields. Recently, we have developed several atomistic molecular dynamics simulation frameworks (Yang et al, 2018;Halonen et al, 2019;Neefjes et al, 2022) to determine collision probabilities from sampling trajectories of atoms or molecules, which predict enhanced collision rate coefficients in good agreement with experiments (Lehtipalo et al, 2016;Stolzenburg et al, 2020). However, as the adequate sampling of collision probabilities requires simulating a large number of binary collisions, these approaches are computationally expensive.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“… 67 This additional attractive potential between the ion and the neutral molecule increased the collision cross-sectional area and alter the angle of collision between the ion and neutral molecule. Furthermore, preliminary molecular dynamic simulations following Neefjes et al 68 suggest a higher collision rate constant for acetate ions (with and without water ligand) with sulfuric acid compared to nitrate dimer ion due in part to acetate’s dipole moment. A forthcoming molecular dynamic simulation study will examine the role ion’s dipole and composition play on collision rate constants with molecular dipoles.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we explore issues related to both obtaining and maintaining thermal equilibrium when performing MD simulations of bimolecular reactions in the gas phase, close to the free molecular regime. 32,33 We focus on simulations of flexible molecular compounds with explicit internal dof, i.e., vibrational modes. First, to study issues related to establishing thermal equilibrium and equipartitioning, we tested the often-used Nosé-Hoover, Canonical Sampling through Velocity Rescaling, and Langevin thermostats, using a system of 30 As the aim of this study is primarily methodological, the potential problems related to thermostatted simulations are investigated using a computationally inexpensive classical force field approach, rather than a chemically more realistic reactive force field or a quantum mechanical description of the compounds and their interactions.…”
Section: Introductionmentioning
confidence: 99%